2007
DOI: 10.1111/j.1467-9280.2007.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in the Impact of Social Support on Psychological and Biological Stress Responses

Abstract: Social support is believed to be a universally valuable resource for combating stress, yet Asians and Asian Americans report that social support is not helpful to them, resist seeking it, and are underrepresented among recipients of supportive services. We distinguish between explicit social support (seeking and using advice and emotional solace) and implicit social support (focusing on valued social groups) and show that Asians and Asian Americans are psychologically and biologically benefited more by implici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
345
5
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 354 publications
(374 citation statements)
references
References 29 publications
20
345
5
4
Order By: Relevance
“…Pregnant women hoped for care that met their personal as well as practical needs, and this might be from a person, a social organisation, a public institution, or a combination of all entities. At the same time, while women emphasised that support came from diverse quarters, they thought that the partner – the biological father – should be present to support and care for them throughout their pregnancy [44]. Some women felt that their partners did not understand what kinds of support and care they needed during pregnancy; they explained this in terms of conventional ideas of masculinity that conflated ideas of what a man is ‘supposed’ to do: take care of everything financially, but not by providing emotional support [45–47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women hoped for care that met their personal as well as practical needs, and this might be from a person, a social organisation, a public institution, or a combination of all entities. At the same time, while women emphasised that support came from diverse quarters, they thought that the partner – the biological father – should be present to support and care for them throughout their pregnancy [44]. Some women felt that their partners did not understand what kinds of support and care they needed during pregnancy; they explained this in terms of conventional ideas of masculinity that conflated ideas of what a man is ‘supposed’ to do: take care of everything financially, but not by providing emotional support [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…Financial challenges [44] and marital status [46] were issues that we anticipated from our participants and other studies [14,41,54]. Many of the women interviewed had limited sources of income to sustain them, but although they spoke about their need for money, this was not the primary support that they identified they needed from their relationships and in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Building on this finding, Taylor et al (2007) investigated outcomes of seeking different types of social support, focusing on cortisol response to an acute lab stressor. This study showed that experimentally instructing participants to explicitly seek social support increased cortisol responses (i.e., higher biological stress) to the lab stressor among Asian Americans, but such an increase was not found among European Americans.…”
Section: Culture and Physiological Processesmentioning
confidence: 99%
“…Biological responses are no exception. Research finds cultural differences in neuroendocrine and immune reactions to an array of intrapersonal and interpersonal tasks (e.g., Cohen et al, 1996;Heejung Kim, 2008;Stephens, Townsend, Markus, & Phillips, 2012;Taylor, Welch, Kim, & Sherman, 2007).…”
Section: Culture and Physiological Processesmentioning
confidence: 99%
“…This cultural difference emerges with both open-ended assessments and standard coping inventories (20). The effectiveness of support seeking also varies cross-culturally, as it can have a negative impact on the psychological and biological stress responses of Asians responding to laboratory stressors (23). This cultural difference occurs because Asians are more concerned about the potential negative relational implications of support seeking than are European Americans (20,21).…”
mentioning
confidence: 99%